2012
DOI: 10.1590/s0006-87052012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in clones of 'Prata Anã' bananas based on phenotypic and molecular markers

Abstract: The objective of this study was to examine the molecular and phenotypic variability of 'Prata Anã' banana clones cultivated in northern Minas Gerais State. For the phenotypic and molecular characterization, the clones were collected from five properties. The morphological characterization of 20 clones was accomplished through a qualitative evaluation of 74 descriptors. For the molecular evaluations, 45 clones were collected, and 14 Random Amplified Polymorphic DNA primers were used. Among the 74 morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
5
0
5
Order By: Relevance
“…In each ISSR reaction, the total number of amplified fragments ranged from three (UBC-810 and UBC-864) to eight (UBC-817 and UBC-826), with a mean number of six bands per primer (Table 2 and Figure 1). Lower levels of polymorphism (33 and 34%) were found in banana Prata-Anã genotypes by Lopes et al (2014) and Rodrigues et al (2012), respectively, using RAPD molecular markers. In a study on Musa ssp cultivars, Ying et al (2011) identified a high percentage of polymorphism (85.1%) using ISSR markers.…”
Section: Resultsmentioning
confidence: 83%
“…In each ISSR reaction, the total number of amplified fragments ranged from three (UBC-810 and UBC-864) to eight (UBC-817 and UBC-826), with a mean number of six bands per primer (Table 2 and Figure 1). Lower levels of polymorphism (33 and 34%) were found in banana Prata-Anã genotypes by Lopes et al (2014) and Rodrigues et al (2012), respectively, using RAPD molecular markers. In a study on Musa ssp cultivars, Ying et al (2011) identified a high percentage of polymorphism (85.1%) using ISSR markers.…”
Section: Resultsmentioning
confidence: 83%
“…Rodrigues et al (2012) identificaram variabilidade genética entre clones de bananeira-'Prata-Anã' por meio de marcadores RAPD e encontraram porcentagem de bandas polimórficas (34%) similar à deste trabalho.…”
Section: Resultsunclassified
“…Como todos os genótipos avaliados são da 'Prata-Anã', sugere-se, com a obtenção dessas distâncias, serem variantes somaclonais. Outros autores em caracterização de clones de bananeira também encontraram distâncias genéticas altas entre os genótipos avaliados, o que demonstra a existência de variações somaclonais (LIBRELON et al, 2013;RODRIGUES et al, 2012;GUBBUK et al, 2004). Em bananeira, ocorrem variações somaclonais em nível muito superior ao que se observa na maioria das outras culturas (provavelmente, devidas à instabilidade mitótica), principalmente em cultura de tecidos, que são também observadas no campo (SILVA et al, 2002), revelando então essa alta variabilidade genética entre elas.…”
Section: Resultsunclassified
“…Embora Rodrigues et al (2012), ao realizarem a caracterização de 45 clones de bananeira 'Prata-Anã' por meio do uso de marcadores RAPD, incluindo os clones estudados neste trabalho, tenham observado variabilidade entre os materiais, todos os clones avaliados agruparam-se com a cultivar Prata-Anã. …”
Section: Resultsunclassified
“…Rodrigues et al (2012) demonstraram em seu estudo que a presença de antocianina no pseudocaule, a forma do cacho e a flexão das pencas permitiram diferenciar de maneira clara os clones de 'Prata-Anã Gorutuba' da cultivar comercial Prata-Anã.…”
Section: Introductionunclassified